Fisica e metafisica del sublime in Barnett Newman (Itinera, 2021)
The main aim of the article is to explore the conceptual genesis of Barnett Newman’s artistic «sublime». To do this, ample attention is paid to a 1947 critical text in which Newman articulates in philosophical terms a polarity that will rest fundamental in his pictorial practice: that between the “transcendence of objects” and the “reality of transcendental experience”. Generated in Newman’s reflection in order to detach his own painting from the great abstract European tradition, the idea behind that dichotomy served as a laboratory for the well-known essay Sublime is Now (1948). The article attempts to make explicit the fundamental convergence of metaphysical and physical instances in the artist’s personal notion of the sublime, which links to a radical rethinking of the relationship between subject and object in painting.
Keywords: Newman, Painting, Sublime, Kant, Abstraction